Inventory of the aquatic entomofauna from the Padilla Creek, tributary of Honda 's aqueduct (Tolima) - VERGARA-RUIZ, RODRIGO A.; GÓNGORA, FRANCISCO J.; PRIETO, MIGUEL A.; GALEANO-OLAYA, PEDRO E. (Revista Colombiana de Entomología, 1994)
The quality of the water that serves as a city 's water supply is a characteristic that determines in part the life conditions of its inhabitants. Because of this, during 1990 this study was developed with the purpose to recognize and classify the aquatic insects that together with other macroinvertebrates, would serve to calculate the biotic indexes, diversity measures, and based on these values, to determine the water quality. Five sampling sites from the creek' s start until the end was chosen and in which collects of entomofauna were made in 15 opportunities, every 15 days. Samples were obtained using sweep nets, shovels, and nets. The water state from the creek was studied based on the methodologies and indexes of Margalef and Hilsenhoff. Specimens from 32 families, 26 genera and 36 species were obtained. The most representative families were: Hydropsychidae (Trichoptera) with 14.36% of the total captured insects; Coenagrionidae (Odonata) 6.31% and Leptophlebiidae (Ephemeroptera) with 6.13%. From the ten recognized orders, the one with the greatest number of families was Hemiptera with seven: Naucoridae, Nepidae, Hydrometridae, Veliidae, Belostomatidae, Gerridae, and Notonectidae. The genera Leptonema (Trichoptera: Hydropsychidae), Dromogomphus (Odonata: Gomphydae), and Polycentropus (Trichoptera: Polycentropidae) were notorious because of their abundance. The biotic and diversity indexes had 1.92 and 3.36 average values, respectively, and they permit to establish that this water body is in the category of good and clear water.